Severe pulmonary infections complicating nivolumab treatment for lung cancer: a report of two cases. Issue 4 (3rd July 2020) - Inthasot, Valentine; Bruyneel, Marie; Muylle, Inge; Ninane, Vincent
ABSTRACT: Background: Immunotherapy represents a recent milestone in the treatment of lung cancer, particularly with the rapidly expanding development of monoclonal antibodies targeting checkpoint inhibitors in the programmed cell death-1 (PD-1) pathway, such as nivolumab and pembrolizumab. Classical auto-immune side effects of these treatments, often called immune-related adverse events (irAEs), can affect multiple organs, including the lungs in which potentially life-threatening pneumonitis may require rapid treatment with high doses of corticosteroids. Nevertheless, the occurrence of severe infections in cancer patients treated with nivolumab, outside the context of immunosuppressive therapy, is a complication that has rarely been reported in the literature. Clinical cases: We report two cases of severe pulmonary infection with unusual microbes, Mycobacterium tuberculosis and Aspergillus fumigatus, in patients treated with nivolumab for non-small cell lung cancer. Conclusion: Ruling out pulmonary infections may require extensive investigation, as these may have an atypical presentation due to immunomodulation. Furthermore, treating the patient with corticosteroids for immune-related pneumonia could lead to a fatal outcome in this context. This report highlights the importance of excluding the presence of opportunistic infections and tuberculosis before considering immune-related pulmonary toxicity with or without a history of prior corticosteroid use. These cases also emphasize the potential value of tuberculosis screening in patients treated with PD-1 checkpoint inhibitors.